1992
DOI: 10.1093/jn/122.11.2101
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Marginal and Copper-Deficient Diets Decrease Aortic Prostacyclin Production and Copper-Dependent Superoxide Dismutase Activity, and Increase Aortic Lipid Peroxidation in Rats

Abstract: Agonist challenged aortic prostacyclin production was examined in copper-adequate, -marginal and -deficient rats fed AIN-based diets providing 6.7, 1.7 and 0.8 micrograms Cu/g, respectively. Aortic rings were incubated in Krebs-Henseleit salts, 10 mmol/L HEPES buffer, pH 7.4, 95%:5% O2:CO2, 37 degrees C, and equilibrated for 1 h. Equilibrated rings were challenged with buffer (basal), 273.0 nmol/L thrombin and angiotensin II at 84.6 pmol/L and 846.0 pmol/L. Prostacyclin production, determined at 10 minutes by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…A substantial amount of support exists for an oxidative mechanism of copper deficiency-induced heart damage. This includes inhibition of cardiac defects by antioxidants (Saari, 1989), increased susceptibility of mitochondria to in vitro oxidation (Akers and Saari, 1993;Bode et al, 1992;Nelson et al, 1992), enhanced tissue damage with oxidative stress (Jenkinson et al, 1984), and increased lipid peroxidation (Balevska et al, 1981) in copper-deficient animals. In studies to determine the role of oxy-radicals in copper deficiencyinduced heart hypertrophy, dimethyl sulfoxide (DMSO), an antioxidant, was administered (Saari, 1989).…”
Section: Ietary Copper Restriction Results In Retardedmentioning
confidence: 99%
“…A substantial amount of support exists for an oxidative mechanism of copper deficiency-induced heart damage. This includes inhibition of cardiac defects by antioxidants (Saari, 1989), increased susceptibility of mitochondria to in vitro oxidation (Akers and Saari, 1993;Bode et al, 1992;Nelson et al, 1992), enhanced tissue damage with oxidative stress (Jenkinson et al, 1984), and increased lipid peroxidation (Balevska et al, 1981) in copper-deficient animals. In studies to determine the role of oxy-radicals in copper deficiencyinduced heart hypertrophy, dimethyl sulfoxide (DMSO), an antioxidant, was administered (Saari, 1989).…”
Section: Ietary Copper Restriction Results In Retardedmentioning
confidence: 99%
“…Support for the view that copper deficiency causes peroxidative damage has been reviewed [18]. The primary observations that support the presence of oxidative stress in copper deficiency are the reduction in activities of several copper-dependent antioxidant enzymes, superoxide dismutase, ceruloplasmin and cytochrome c oxidase, and possibly non-copper-dependent enzymes such as catalase [19,20] These findings have been complemented by observations of increased peroxidative products in blood, tissues and exhaled breath [21][22][23] by increased susceptibility to oxidative damage in copperdeficient animals [24] by correlation of severity of the defects with extent of peroxidation [25] and by amelioration of defects by treatment with antioxidants [26] or by transgenically elevating oxidant status [27]. A possible consequence of the pro-oxidant status of Cu-deficient animals is the upregulation of the COX-2 enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…These workers also found increased thiobarbituric acid-reactive substances in heart and liver tissues from Cu-deficient rats while Nelson et al (1992) found increased aortic lipid peroxides (malondialdehyde equivalents) in rats fed on Cu-marginal and Cu-deficient diets, the latter increase being associated with depressed aortic CuZn-SOD activity.…”
Section: Copper a N D Atherosclerosismentioning
confidence: 93%